Alleviating Role of Gibberellic Acid in Enhancing Plant Growth and Stimulating Phenolic Compounds in Carrot (Daucus carota L.) under Lead Stress - Muhammad Awais Ghani (MDPI AG, 2021)
Toxicity of heavy-metals in soil is a major constraint for the production of carrots (Daucus carota L.). Different plant growth regulators are being used to overcome this problem. It has been found that plant growth regulators induce stress tolerance in plants. In this study, the role of exogenously applied plant growth regulator, gibberellic acid (GA3) was examined in soil grown two carrot cultivars under four different levels of lead (0, 50, 100, and 150 mg/kg) with one level of gibberellic acid (50 ppm). Results showed that Pb stress retarded the plant growth and reduced chlorophyll contents in the leaves of both carrot cultivars. A significant decrease was observed in photosynthetic attributes by Pb addition alone. However, exogenously applied GA3 ameliorated the plant growth and chlorophyll contents in the leaves of both carrot cultivars under Pb stressed conditions. Moreover, GA3 also decreased the uptake of Pb concentration in carrot leaves and roots. In addition, GA3 significantly regulated the phenolic compounds concentration in both carrot cultivars under Pb stress. In this study, cultivar T-29 was found to be more tolerant to Pb stress, however, cultivar Mevarick experienced higher damage regarding plant growth under Pb stress.